Evaluation of the cost per patient per injection of botulinum toxin A in upper limb spasticity: comparison of two preparations in 19 countries - Valentine W (Dove Medical Press, 2012)
Stéphane Roze,1 Hannah Kurth,2 Barnaby Hunt,3 William Valentine,3 Rémi Marty11HEVA, Lyon, France; 2Ipsen Pharma, Boulogne-Billancourt, France; 3Ossian Health Economics and Communications, Basel, SwitzerlandBackground: Botulinum toxin A injections are indicated for the management of movement disorders, including upper limb spasticity. The aim of this study was to compare the cost per patient per injection for two botulinum toxin A preparations in 19 countries.Methods: Doses of botulinum toxin A are expressed in noninterchangeable units (U), ie, Botox® in 100 Allergan units (100 U) and Dysport® in 500 Speywood units (500 U). Recommended dosages were derived from country-specific summaries of product characteristics or prescribing information. Cost analysis was based on official list prices and expressed in 2011 Euros. The cost per patient per injection was calculated using the recommended dosage in upper limb spasticity combined with price per vial in each country.Results: For upper limb spasticity, the recommended dosage for Dysport in the summary of product characteristics is 1000 U per patient, whereas for Botox the recommended dosage when recommendations were made is 300 U. Allowing for different prices per vial in each country, the cost per patient per injection for upper limb spasticity was less for Dysport than for Botox in 18 (95%) of the 19 countries (mean 17% less across countries). The difference was 20% or higher in nearly half (47%) of the countries. Sensitivity analyses considering available "real-world" dosing showed consistent results, with Dysport being less costly than Botox in all 19 countries.Conclusion: Considering costs per patient per injection based on analysis of recommended dosages in the summary of product characteristics, Dysport remains cheaper than Botox in most countries. Thus, when extrapolated to a national level, substantial savings could be realized by using Dysport in the treatment of upper limb spasticity.Keywords: upper limb spasticity, stroke, botulinum toxin, Dysport®, Botox®